2022
DOI: 10.3390/ijerph192316304
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden, Psychological Distress and Quality of Life among Informal Caregivers of Patients with Head and Neck Cancer: A Longitudinal Study

Abstract: (1) Background: The aim of this study was to investigate caregiver burden among informal caregivers of head and neck cancer patients, in relation to distress and quality of life (QoL), and the relationship between informal caregivers and patients. (2) Methods: Data of 234 dyads from the multicenter prospective cohort study Netherlands Quality of life and Biomedical Cohort studies in cancer was used. Caregiver burden, psychological distress, global QoL, physical and social functioning were measured from baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…When addressing self-efficacy and coping style, special attention should be given to caregivers with higher age, females, and/or lower education, as these factors were associated with less self-efficacy and "active tackling." Providing psychological interventions is not only important for the caregivers themselves, but also for the HNC patients, as in a prior study we found that reduced functioning of informal caregivers was associated with reduced functioning of patients related to them [10]. In a review of Cheng et al, short-term effects of psychoeducational interventions were found on caregivers' psychological distress, quality of life, caregiver burden, and self-efficacy [49].…”
Section: Clinical Implications and Future Perspectivesmentioning
confidence: 57%
See 1 more Smart Citation
“…When addressing self-efficacy and coping style, special attention should be given to caregivers with higher age, females, and/or lower education, as these factors were associated with less self-efficacy and "active tackling." Providing psychological interventions is not only important for the caregivers themselves, but also for the HNC patients, as in a prior study we found that reduced functioning of informal caregivers was associated with reduced functioning of patients related to them [10]. In a review of Cheng et al, short-term effects of psychoeducational interventions were found on caregivers' psychological distress, quality of life, caregiver burden, and self-efficacy [49].…”
Section: Clinical Implications and Future Perspectivesmentioning
confidence: 57%
“…Also, high depression levels of caregivers may negatively influence patients quality of life (QoL) during long-term follow-up [10].To provide optimal support, insight into the way people deal with a certain situation is needed which can be divided in skills of self-efficacy and coping mechanisms. Self-efficacy has been defined as the confidence in your own ability to influence successful outcomes in challenging or stressful situations [11].…”
Section: Highlightsmentioning
confidence: 99%
“…Previous cross-sectional studies indicate that the unmet supportive care needs of caregivers of HNC patients can lead to an increased caregiver burden, emotional distress, and a reduced QoL [13,17]. The psychological distress felt by informal caregivers is related to the HNC patient's QoL and psychological distress [8,18]. Caregivers' unmet needs can undermine the support they can provide to the patient and may even lead to psychological or medical problems in the caregivers themselves [17].…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers' unmet needs can undermine the support they can provide to the patient and may even lead to psychological or medical problems in the caregivers themselves [17]. The fact that unmet supportive care needs are related to psychological distress, and that informal caregivers' psychological distress is related to patients' functioning, underlines the importance of offering supportive care to caregivers [8,18]. Despite this, there is a lack of longitudinal long-term follow-up studies regarding the unmet needs of HNC caregivers [19,20].…”
Section: Introductionmentioning
confidence: 99%
“… 6 According to multisystem theory, patients are not independent individuals but are part of a system of interaction with their informal caregivers. 7 FCs are companions, children or close friends who have a significant personal relationship with the patient, all of whom provide a broad range of assistance for the person with a chronic or disabling condition, such as HNC. 8 Caregivers, as well as patients, may be adversely affected by cancer, and patients with cancer rely on the emotional, physical and financial support of their caregivers.…”
Section: Introductionmentioning
confidence: 99%